(untitled) (Eurasian Medical Research Periodical, 2023)
According to modern ideas, the growth of the facial skeleton and skull in norm is caused by many factors. It is genetically determined. The implementation of the genetic programme of harmonious growth of facial bones and jaws depends on the correct structure of the hereditary genome, the normal course of prenatal and postnatal ontogenesis. In congenital clefts many links of this mechanism of facial skeleton growth are disturbed